Light-induced magnetoresistance in solution-processed planar hybrid devices measured under ambient conditions - Banerjee, Sreetama; Bülz, Daniel; Reuter, Danny; Hiller, Karla; Zahn, Dietrich R. T.; Salvan, Georgeta (Beilstein Journal of Nanotechnology, 2017)
We report light-induced negative organic magnetoresistance (OMAR) measured in ambient atmosphere in solution-processed 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-pentacene) planar hybrid devices with two different device architectures. Hybrid electronic devices with trench-isolated electrodes (HED-TIE) having a channel length of ca. 100 nm fabricated in this work and, for comparison, commercially available pre-structured organic field-effect transistor (OFET) substrates with a channel length of 20 µm were used. The magnitude of the photocurrent as well as the magnetoresistance was found to be higher for the HED-TIE devices because of the much smaller channel length of these devices compared to the OFETs. We attribute the observed light-induced negative magnetoresistance in TIPS-pentacene to the presence of electron–hole pairs under illumination as the magnetoresistive effect scales with the photocurrent. The magnetoresistance effect was found to diminish over time under ambient conditions compared to a freshly prepared sample. We propose that the much faster degradation of the magnetoresistance effect as compared to the photocurrent was due to the incorporation of water molecules in the TIPS-pentacene film.
Keywords: HED-TIEs; hybrid electronic devices; organic field-effect transistors (OFETs); organic magnetoresistance; planar hybrid devices; TIPS-pentacene

(untitled) - Dediu, V. A.; Hueso, L. E.; Bergenti, I.; Taliani, C. (Nat. Mater., 2009)

(untitled) - Wohlgenannt, M. (Phys. Status Solidi RRL, 2012)

(untitled) - Mermer, Ö.; Veeraraghavan, G.; Francis, T. L.; Wohlgenannt, M. (Solid State Commun., 2005)

(untitled) - Zhang, S.; Rolfe, N. J.; Desai, P.; Shakya, P.; Drew, A. J.; Kreouzis, T.; Gillin, W. P. (Phys. Rev. B, 2012)

(untitled) - Reichert, T.; Saragi, T. P. I. (Appl. Phys. Lett., 2011)

(untitled) - Martin, J. L.; Bergeson, J. D.; Prigodin, V. N.; Epstein, A. J. (Synth. Met., 2010)

(untitled) - Hu, B.; Wu, Y. (Nat. Mater., 2007)

(untitled) - Francis, T. L.; Mermer, Ö.; Veeraraghavan, G.; Wohlgenannt, M. (New J. Phys., 2004)

(untitled) - Reichert, T.; Saragi, T. P. I. (Org. Electron., 2012)

(untitled) - Murtaza, G.; Ahmad, I.; Chen, H.; Wu, J. (Synth. Met., 2014)

(untitled) - Feng, L.; Tang, W.; Zhao, J.; Yang, R.; Hu, W.; Li, Q.; Wang, R.; Guo, X. (Sci. Rep., 2016)

(untitled) - Banerjee, S.; Bülz, D.; Solonenko, D.; Reuter, D.; Deibel, C.; Hiller, K.; Zahn, D. R. T.; Salvan, G. (Nanotechnology, 2017)

(untitled) - Mermer, Ö.; Veeraraghavan, G.; Francis, T. L.; Sheng, Y.; Nguyen, D. T.; Wohlgenannt, M.; Köhler, A.; Al-Suti, M. K.; Khan, M. S. (Phys. Rev. B, 2005)

(untitled) - Wagemans, W.; Koopmans, B. (Phys. Status Solidi B, 2011)

(untitled) - Vollmer, A.; Jurchescu, O. D.; Arfaoui, I.; Salzmann, I.; Palstra, T. T. M.; Rudolf, P.; Niemax, J.; Pflaum, J.; Rabe, J. P.; Koch, N. (Eur. Phys. J. E, 2005)

(untitled) - Jurchescu, O. D.; Baas, J.; Palstra, T. T. M. (Appl. Phys. Lett., 2005)